Internal audit in small local governments in Latvia - Faitusa, Ivita (Kaunas University of Technology, 2017)
Research background The role of internal audit is to provide independent assurance that an organisation’s risk management, governance, and internal control processes are operating effectively. Purpose of the article The purpose of the article was to substantiate the significance of the internal audit function and the relationship between indicators in financial statement (revenue and balance sheet value) and the existence of the internal audit function in local governments in Latvia and to find out internal audit approaches for small local governments. Methodology/methods This study used the quantitative case study approach, financial statement (data) analysis, the Kolmogorov-Smirnov test, the Kruskal-Wallis test, the Mann-Whitney test, and the monographic method. Findings The research elucidated that the relationship between financial indicators like revenue and balance sheet values of local governments in Latvia differed significantly with high probability in the years 2013, 2014, and 2015, as evidenced in the Kruskal-Wallis test. Revenue and balance sheet values in local governments with the internal audit function differed significantly as the Mann-Whitney test results proved Conclusions The article suggests making changes and amendments to the legislation that should be supplemented with special conditions for local governments, that is, implementation of the internal audit depending on the revenue and the balance sheet value of a local government and a number of inhabitants in that local government.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; internal audit; local government